Digital Engagement Among the Jamaah Tabligh in Nigeria and Indonesia: A Comparative Analysis of Social Media Usage - Abdrahman Ismail, Abolaji (Digital Muslim Review, 2025)
The Jamā'ah Tablīgh, a transnational movement built on physical missionary work, increasingly navigates digital spaces in ways that challenge its traditional ethos. This article compares how the movement engages social media in Nigeria and Indonesia through a systematic review of ethnographic studies and media reports. Findings reveal significant divergence: Nigerian Tablīghīs employ closed platforms like WhatsApp and memory cards for internal coordination, prioritizing audio to minimize visual distraction and maintain the movement's oral tradition. Indonesian Tablīghīs cultivate public presences on Facebook, Instagram, and YouTube for transnational coordination, community documentation, and strategic rebranding against negative stereotypes. Despite these differences, both communities share fundamental orientations—treating digital tools as instruments for da'wah rather than alternatives to embodied practice, maintaining wariness of fitna, and prioritizing internal community building. The article argues these patterns represent local adaptations of a shared transnational ethos, revealing digital engagement as active appropriation rather than passive adoption. The study contributes to digital religion scholarship by complicating secularization narratives and showing how conservative movements creatively integrate technology to preserve—rather than abandon—traditional commitments to khurūj (missionary journeys) and face-to-face preaching.